2022
DOI: 10.1002/pon.6023
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors influencing demoralization among cancer patients based on the bio‐psycho‐social model: A systematic review

Abstract: Objective: Demoralization is a prevalent psychological problem among cancer patients and reflects a sense of subjective incompetence. This systematic review aims to identify factors influencing demoralization among cancer patients.Methods: Eleven databases were systematically searched from database inception to 31 December 2020. Google Scholar and relevant reference lists were supplementarily searched. Studies reporting demoralization measured by Demoralization Scale and its influencing factors among cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…Quality of life is an important factor that may have a bi-directional relationship with demoralization in cancer patients [23,24]. However, the negative associations with breast cancer remain unclear.…”
Section: Demoralization and Its Association With Quality Of Life Slee...mentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of life is an important factor that may have a bi-directional relationship with demoralization in cancer patients [23,24]. However, the negative associations with breast cancer remain unclear.…”
Section: Demoralization and Its Association With Quality Of Life Slee...mentioning
confidence: 99%
“…Extant literature distinguishes between demoralization and depression; however, the two are strongly correlated in cancer patients [17,[30][31][32][33][34]. Depression and demoralization are both high-risk factors for suicide in cancer patients, and patients with both are at higher risk [23,24,35]. Demoralization is independently associated with suicide after controlling for the severity of depression [36].…”
Section: Demoralization and Its Association With Quality Of Life Slee...mentioning
confidence: 99%
“…19 Hong et al further identified factors associated with demoralization in cancer patients, which included advanced tumour stages. 20 The eligible criteria in these studies did not exclude patients with advanced cancer. The primary hypothesis of our study was that cancer survivors might also be vulnerable to demoralization as much as other cancer patients undergoing active treatment or palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al . further identified factors associated with demoralization in cancer patients, which included advanced tumour stages 20 . The eligible criteria in these studies did not exclude patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, physical symptoms have emerged as a potent influencing factor for demoralization. 18 Moreover, higher resilience and positive family functioning may boost adaptive coping strategies, resulting in reduced distress in cancer patients. 19,20 Despite these findings, previous research has yet to shed light on the factors influencing the latent classes of demoralization in lung cancer patients.…”
mentioning
confidence: 99%